ChemInform Abstract: Iron‐Catalyzed N‐Arylsulfonamide Formation Through Directly Using Nitroarenes as Nitrogen Sources. Issue 34 (August 2015) - Zhang, Weixi; Xie, Junyao; Rao, Bin; Luo, Meiming
Abstract Nitromethane as well as sodium benzylsulfinate do not react.